أدوار مستشار التوجيه والارشاد المدرسي والمهني فى الوقاية من تعاطي التلاميذ للمخدرات في الوسط المدرسي - بن عيشة,امنة; بيكي,سارة (My University, 2024)
This study aimed to know the roles of school and vocational guidance and counseling counselors in preventing students’ drug addiction in the school environment from the point of view of school and vocational guidance and counseling counselors. Based on the exploratory approach, the study was conducted on a sample of 28 guidance counselors, one male and one female. 2males and 26.females, and using the corresponding data collection tool, the following results were reached: The guidance counselor works to place publications in the comments that enrich students with information about the dangers of drugs and how to prevent them, and to distribute brochures that include an introduction to drugs and their dangers and how to prevent them, and psychological follow-up of students who suffer from family, educational, and social problems in order to enable them to overcome them and conduct classes. Media to address and prevent this phenomenon to prevent its spread in the school environment, prepare preventive programs and use appropriate guidance methods and techniques to address this problem and contribute to discovering students who abuse and students who are vulnerable to abuse. هدفت هذه الدراسة معرفة أدوار مستشار التوجيه و الإرشاد المدرسي و المهني في الوقاية من تعاطي التلاميذ للمخدرات في الوسط المدرسي من وجهة نظر مستشاري التوجيه و الإرشاد المدرسي و المهني، و بالاعتماد على المنهج الاستكشافي تم إجراء الدراسة على عينة مكونة من مستشارين التوجيه28 مستشار و مستشارة منهم 2 ذكور و 26 إناث وباستخدام أداة جمع البيانات المقابلة تم التوصل للنتائج التالية : -تتمثل الأدوار الواقئية لمستشار التوجيه في: نشر المعلقات التي تثري التلاميذ بالمعلومات عن المخاطر المخدرات وكيفية الوقاية منها، و بتوزيع المطويات التي تتضمن التعريف بالمخدرات و مخاطرها وكيفية الوقاية منها، و المتابعة النفسية للتلاميذ الذين يعانون من مشاكل أسرية و تربوية و إجتماعية، قصد تمكين من تجاوزها وإجراء حصص إعلامية لتصدي للتلاميذ و أوليائهم والوقاية من هذه المشكلة لمنع تفشها في الوسط المدرسي وإعداد برامج وقائية وإستخدام أساليب وفنيات إرشادية مناسبة للتصدي لهذه المشكلة والمساهمة في إستكشاف التلاميذ الذين يتعاطون و التلاميذ الذين هم عرضة للتعاطي.
من وجهة نظر مستشاري التوجيه و الارشاد المدرسي و المهني
Keywords: مستشار التوجيه; المخدرات; Guidance counselor; Drugs